Understanding the Coevolution between Institutional and Business Dynamics: A Longitudinal Study in Taiwanese Business Groups - Lin, Hung (2008)
Business groups are a special type of enterprise systems existing in almost every emerging economy, and act as the microeconomic agents of industrial growth in many successful late-industrialising countries in the 20th century. Because the groups are important and pervasive, a large number of related researches have been undertaken from different disciplinary angles, such as economic and sociological views. Despite these abundant studies, little attention has been paid to the dynamic nature of the business group strategies. Focusing on the longitudinal studies on the evolutionary patterns of two different strategies in three Taiwanese business groups during the institutional transitions, this research integrates the static views of group strategies and advances the understanding of the coevolving institutional and business dynamics. The findings not also support Peng's hypothesis that the group strategies will move from relationship-based to market-based model as the institutions modernise, but also propose that this evolutionary pattern is irregular due to the dynamics of institutional changes. Furthermore, the evidence indicates that the relationship-based strategy may become more important when the uncertainty of institutional environment intensifies, but may turn invalid when a dramatic change takes place in the political regime. Overall, this article contributes to the literature on the dynamic relationship between business group strategies and institutional environment over time.